Pattern of lipid levels of subjects seeking laboratory services in an established laboratory in the Dhaka city (Bangladesh Journal of Medical Science, 2017)
Background: Dyslipidemia is linked to the risk for coronary ischemic and cardiovascular disease. Considering the absence of national reference level for lipids in Bangladesh the present study was undertaken to look into the pattern of lipid levels among patients seeking laboratory services in a private medical college hospital.Materials and Methods: This cross sectional study was carried out in Ibn Sina Medical College Hospital in Dhaka city. Patients with antilipid and other medication which might affect the outcome were excluded. Consenting and eligible subjects seeking laboratory services were included in the study. Total 970 subjects finally entered in the study. Total cholesterol [TC], triglyceride and HDL-cholesterol [HDL-c] were measured by enzymatic colorimetric method. LDL-cholesterol [LDL-c] was derived using Friedewald equation. Data were expressed mean±SD, number (percent) as appropriate. Statistical analyses were carried out using SPSS version 17 tool. A p value